Clinical significance of p53, K-ras and DCC gene alterations in the stage I-IIcolorectal cancers - (:unkn) unknown (MEDICAL UNIV PRESS, 2007)
Background and aims. Genetic alterations of p53, K-ras and DCC genes have a pivotal role in the colorectal cancer progression. The aim Of this study was to clarify the association between K-ras mutations, p53 aberrations and DCC loss of heterozygosity (LOH), with the patient outcome and tumor characteristics in 43 stage I-II colorectal cancer patients. Methods. Mutations in exons 5-8 of the p53 gene and codon 12 and/or 13 of the K-ras gene were assayed by PCR-SSCP and then confirmed by DNA sequencing. DCC LOH Was studied by PCR-RFLP, while p53 immunohistochemistry was also made. Results. Mutations of the p53 gene were found in 14 (32.5%) tumors. Five (12%) cases showed mutations of the K-ras gene. Nuclear staining of p53 was found in 22 (51 %) cases. DCC LOH was found in 5 (12%) cases. Cases With guanine to thymine substitution that occurred in K-ras codon 12 and DCC LOH were found to be more aggressive than other cases with codon 12 mutations or DCC wild-type phenotype. Many tumors with p53 over-expression were localized on the left side of the colon (p=0.005). The stage of the tumor was higher in patients who died during the follow-up period, when compared to the ones who have survived. Conclusions. Although none of these genetic alterations showed a significant prognostic value, Specific Mutation of K-ras gene and DCC LOH phenotype might have a predictive prognostic implication in colorectal cancer. Furthermore, different etiopathogenetic mechanisms might be involved in the tumorigenesis of the left and right colon.
Keywords: colorectal cancer; p53; K-ras; DCC LOH; prognosis; HUMAN COLORECTAL CANCERS; TUMOR-SUPPRESSOR GENE; TP53 MUTATION; COLON-CANCER; KIRSTEN-RAS; PROGNOSTIC-SIGNIFICANCE; PROTEIN; HETEROZYGOSITY; METASTASIS; CARCINOMAS